Specific changes in conduction velocity recovery cycles of single nociceptors in a patient with erythromelalgia with the I848T gain-of-function mutation of Nav1.7 - Namer, Barbara; Orstavik, Kristin; Schmidt, Roland; Kleggetveit, Inge-Petter; Weidner, Christian; Mork, Cato; Kvernebo, Mari Skylstad; Kvernebo, Knut; Salter, Hugh; Carr, Thomas Hedley; Segerdahl, Marta; Quiding, Hans; et al. (Pain, 2015)
Seven patients diagnosed with erythromelalgia (EM) were investigated by microneurography to record from unmyelinated nerve fibers in the peroneal nerve. Two patients had characterized variants of sodium channel Nav1.7 (I848T, I228M), whereas no mutations of coding regions of Navs were found in 5 patients with EM. Irrespective of Nav1.7 mutations, more than 50% of the silent nociceptors in the patients with EM showed spontaneous activity. In the patient with mutation I848T, all nociceptors, but not sympathetic efferents, displayed enhanced early subnormal conduction in the velocity recovery cycles and the expected late subnormality was reversed to supranormal conduction. The larger hyperpolarizing shift of activation might explain the difference to the I228M mutation. Sympathetic fibers that lack Nav1.8 did not show supranormal conduction in the patient carrying the I848T mutation, confirming in human subjects that the presence of Nav1.8 crucially modulates conduction in cells expressing EM mutant channels. The characteristic pattern of changes in conduction velocity observed in the patient with the I848T gain-of function mutation in Nav1.7 could be explained by axonal depolarization and concomitant inactivation of Nav1.7. If this were true, activity-dependent hyperpolarization would reverse inactivation of Nav1.7 and account for the supranormal CV. This mechanism might explain normal pain thresholds under resting conditions.
EVALuna2:2475